An analysis of communication between health-care workers and Xhosa-speaking patients in a Cape Town hospital, from the perspective of language cognition and inter-cultural communication - Nxasana, Nonceba Thandeka Jacqueline (Centre for Applied Language and Literacy Studies and Services in Africa, 2016)
Includes bibliographical references (pages 78-82).